Comparing the Lexical Density of Spoken and Written News - Mulyati Khorina; Wulandari Zahara Handani (Muhammadiyah University of Mataram, 2022)
This paper is concerned with lexical density in spoken and written news on BBC News. The purpose of this study is to investigate the lexical density found in spoken and written news regarding the Afghanistan and Taliban conflict broadcasted by BBC. The method applied in this study was a qualitative method. The data consist of five spoken news taken from the BBC YouTube channel and five written news obtained from the BBC news website. The results show that generally, the average lexical density levels of both spoken and written news tend to be the same, that is, higher than 50%. Specifically, spoken news has an average lexical density level of 52.15% while written news has an average lexical density of 55.05%. Meanwhile, the lexical items which influence the density of the texts are nouns, verbs, adjectives, and adverbs with the noun to be dominant.